A QUEM CABE A PROTEÇÃO DO VULNERÁVEL? AS CONTRIBUIÇÕES DOS MOVIMENTOS SOCIAIS DA DÉCADA DE 1990 NA LUTA PELA GARANTIA DOS DIREITOS DE CRIANÇAS E ADOLESCENTES - Émina Márcia Nery dos; Andréa Márcia Monteiro (Revista da Faculdade de Educação (Universidade do Estado de Mato Grosso), 2019)
The text aims to analyze the contributions of the social movements in the 1990s to the institution of the rights of children and adolescents in Brazil, especially with regards to the Statute of the Child and the Adolescent (Estatuto da Criança e do Adolescente – ECA). The study results from a bibliographical review, accompanied by content analysis, based on an interview with Father Bruno Sechi, which shows that the public policies of protection in the area of childhood and adolescence evolved considerably from the ECA, but, there are still challenges for public power and civil society. It considers that these rights can be consolidated with the creation of a network of social care that articulates actions between different fields, effecting the protection of children and adolescents with respect to the rights inherent in human existence.